Evaluation of antinociceptive, antinflammatory activities and phytochemical analysis of aerial parts of Urtica urens L. - Marrassini, Carla (2010)
The antinociceptive and antiinflammatory activities of the ethanol extract of the aerial part of Urtica urens were determined by experimental animal models. U. urens extract was found to possess significant antinociceptive activity in chemically induced mouse pain models (ED50 39.3 mg/kg: 17.2-74.5 mg/kg) in the writhing test and 62.8% inhibition of the licking time in the late phase of the formalin test at a dose of 500 mg/kg p.o. and antiinflammatory activity on carrageenan-induced rat hind paw edema (41.5% inhibition at a dose of 300 mg/kg i.p.). The extract displayed activity neither in the thermal model of pain nor in the topical inflammation model. The major component of the extract was determined as chlorogenic acid (670 mg/1000 g dry weight) and could be partly responsible for this activity.